Application of a sponge-like conductive additive in silicon-based negative electrode

CN123017972APending Publication Date: 2026-10-30NANJING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611285879.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,Si与CNT之间的接触有限以及CNT对固态电解质界面SEI的刺穿效应会对性能产生不利影响,具体参见文献“Yong Zhang, Z., Fei Sun, Z., Liu, Y., et al., "Face-to-face conductingmechanism enabled by Si-C bonds for binder free Si@CNTs electrode," ChemicalEngineering Journal 477 (2023): 146504. https://doi.org/10.1016/j.cej.2023.146504.”和“He, Z., Zhang, C., Zhu, Y., Wei, F., "The acupunctureeffect of carbon nanotubes induced by the volume expansion of silicon-basedanodes," Energy & Environmental Science 17 (2024): 3358. https://doi.org/10.1039/d4ee00710g.”;而GN的团聚则会导致其机械性能和电学性能下降,具体参见文献“Punetha, V. D., Rana, S., Yoo, H. J., et al., "Functionalization of carbonnanomaterials for advanced polymer nanocomposites: A comparison study betweenCNT and graphene," Progress in Polymer Science 67 (2017): 1. https://doi.org/10.1016/j.progpolymsci.2016.12.010.”和“Kang, H. E., Ko, J., Song, S. G.,Yoon, Y. S., "Recent progress in utilizing carbon nanotubes and graphene torelieve volume expansion and increase electrical conductivity of Si-basedcomposite anodes for lithium-ion batteries," Carbon 219 (2024): 118800.https://doi.org/10.1016/j.carbon.2024.118800.”

Benefits of technology

[0016]本发明提出的将类海绵导电添加剂应用于锂离子电池硅基负极,类海绵导电添加剂具有以下技术优势:(1)高电导率;(2)良好的可压缩性与回弹性,有助于容留Si基材料在充放电过程中大的体积变化减少电极的体积膨胀、缓解局部应力和硅粉化现象;(3)独特的孔隙结构可作为锂离子储库,通过自呼吸机制调控微米级硅周围的电解液分布,尤其适用于制作微米级硅负极。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017972A_ABST
    Figure CN123017972A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of lithium ion batteries, and discloses application of a sponge-like conductive additive in a silicon-based negative electrode. The sponge-like conductive additive is a hierarchical carbon nanocage material, and the silicon-based negative electrode refers to a kind of negative electrode material taking silicon or a silicon-containing compound as a main active material and realizing energy storage through alloying and de-alloying reactions with lithium. The sponge-like conductive additive is applied to the silicon-based negative electrode of a lithium ion battery, and the sponge-like conductive additive has the following technical advantages: (1) high electrical conductivity; (2) good compressibility and resilience, which is helpful for containing the large volume change of Si-based materials in the charging and discharging process, reducing the volume expansion of the electrode, relieving local stress and silicon powderization; (3) the unique pore structure can be used as a lithium ion storage, and the electrolyte distribution around the micron-sized silicon can be regulated through a self-breathing mechanism, which is especially suitable for manufacturing a micron-sized silicon negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery technology, and specifically discloses the application of a sponge-like conductive additive in silicon-based anodes. Background Technology

[0002] Lithium-ion batteries (LIBs) have been widely used in smart devices and electric vehicles for decades; however, their relatively low energy density remains a significant challenge, causing end-users to continue experiencing range anxiety. Compared to mainstream graphite electrodes, silicon anodes offer a theoretical specific capacity an order of magnitude higher and possess excellent electrochemical performance and cost-effectiveness, making them the preferred material for next-generation lithium-ion batteries. However, the significant volume changes and low conductivity of silicon during lithiation / delithiation processes often lead to severe pulverization and electrolyte consumption, thus limiting the cycle performance of silicon anodes.

[0003] Previous studies have shown that nanostructured silicon (nano-Si) anodes can shorten the bulk diffusion distance of lithium ions and effectively release stress / strain during volume changes, thereby improving specific capacity and cycle stability. In contrast, micron-sized silicon particles (micron-Si) are widely available and inexpensive, and possess advantages such as a small specific surface area to suppress side reactions and high porosity to improve volumetric energy density. However, the lithium storage performance of micron-sized silicon is still severely limited by many adverse factors, such as the elongation of the lithium ion / electron transport path, the localized high stress caused by anisotropic expansion, and the drastic fluctuations in local lithium ion concentration.

[0004] To address these issues, existing technologies primarily focus on improvements in electrode structure, electrolytes, and binders. However, research on conductive agents, which play a crucial role in improving the conductivity of micron-sized silicon anodes, has limitations. While commercially available conductive agents like carbon black (CB) can achieve efficient electron transport through point-contact percolation networks, their solid structure results in poor stress relief. Furthermore, lithiation of silicon materials reduces local lithium-ion concentration and leads to irreversible electrolyte consumption; conversely, delithiation increases the lithium-ion concentration around silicon particles, potentially causing localized lithium-ion deposition. In summary, these phenomena collectively impair cycle stability. For micron-sized silicon anodes, the change in Li⁺ concentration in the electrolyte during lithiation / delithiation is more significant, and carbon-based materials such as CB offer no mitigation for this problem. Figure 1 As shown.

[0005] Recently disclosed conductive additives such as carbon nanotubes (CNTs) and graphene (GN) can enhance electron transport and partially alleviate volume expansion problems due to their high conductivity, high strength and porous network structure. However, the limited contact between Si and CNTs and the puncture effect of CNTs on the solid electrolyte interphase (SEI) can adversely affect performance. See the references “Yong Zhang, Z., Fei Sun, Z., Liu, Y., et al., "Face-to-face conducting mechanism enabled by Si-C bonds for binder free Si@CNTs electrode," Chemical Engineering Journal 477 (2023): 146504. https: / / doi.org / 10.1016 / j.cej.2023.146504.” and “He, Z., Zhang, C., Zhu, Y., Wei, F., "The acupuncture effect of carbon nanotubes induced by the volume expansion of silicon-basedanodes," Energy & Environmental Science 17 (2024): 3358.” https: / / doi.org / 10.1039 / d4ee00710g.”; Aggregation of GN leads to a decrease in its mechanical and electrical properties, as detailed in the literature “Punetha, VD, Rana, S., Yoo, HJ, et al., "Functionalization of carbon nanomaterials for advanced polymer nanocomposites: A comparison study between CNT and graphene," Progress in Polymer Science 67 (2017): 1. https: / / doi.org / 10.1016 / j.progpolymsci.2016.12.010.” and “Kang, HE, Ko, J., Song, SG, Yoon, YS"Recent progress in utilizing carbon nanotubes and graphene to relieve volume expansion and increase electrical conductivity of Si-based composite anodes for lithium-ion batteries," Carbon 219 (2024): 118800. https: / / doi.org / 10.1016 / j.carbon.2024.118800. The aforementioned limitations of CNTs and GNs, along with their inability to control electrolyte composition and distribution, further weaken their performance and practical application value in lithium-ion batteries. Therefore, there is an urgent need to develop novel additive materials to promote electron conduction, stress relief, and electrolyte regulation, thereby solving the serious problems existing in micron-sized silicon anodes. Summary of the Invention

[0006] This invention creatively introduces hierarchical carbon nanocage materials as a sponge-like conductive additive. The hierarchical carbon nanocage material of this invention is a three-dimensional ordered hierarchical conductive network structure with interconnected macropores, mesopores and micropores, which is assembled from individual carbon nanocages (CNC) as basic building blocks. For example, the material hCNC previously disclosed by our research group.

[0007] In a first aspect, the present invention provides an application of a sponge-like conductive additive in a silicon-based anode, wherein the sponge-like conductive additive is the aforementioned graded carbon nanocage material, and the silicon-based anode of the present invention refers to a type of anode material that uses silicon or silicon-containing compounds as the main active material and achieves energy storage through alloying and dealloying reactions with lithium, including any one of micron-sized silicon, submicron-sized silicon, and nano-sized silicon.

[0008] Preferably, the wall thickness of hCNC ranges from 2.5 nm to 3.5 nm.

[0009] When the aforementioned sponge-like conductive additive is used to fabricate silicon-based anodes, especially micron-sized silicon anodes, silicon undergoes significant volume expansion during lithiation. The compressible hierarchical carbon nanocages effectively release stress through inward deformation, while simultaneously significantly suppressing silicon pulverization due to their anti-deformation properties. It is worth noting that, as... Figure 2 As shown, analogous to the liquid absorption / extrusion behavior of natural sponges, the lithium-ion electrolyte stored inside the hierarchical carbon nanocages of this invention can be partially extruded through compression, thereby maintaining a high lithium concentration during the lithiation process; during discharge, Li xAs Si particles shrink in volume, the deformed hierarchical carbon nanocages naturally rebound, maintaining tight electrical contact between the silicon particles and absorbing excess lithium ions within the cavities of the carbon nanocages, effectively suppressing localized lithium salt deposition. It should be noted that the hierarchical carbon nanocage material introduced in this invention, as a sponge-like conductive additive, can be used not only for micron-sized silicon anodes but also for submicron-sized and nano-sized silicon. It is important to clarify that nanostructuring silicon particles only alleviates, rather than completely eliminates, the volume expansion problem; in terms of effectiveness, the hierarchical carbon nanocage material introduced in this invention is most effective for micron-sized silicon anodes.

[0010] Secondly, the present invention provides a composite conductive agent comprising carbon black and the aforementioned sponge-like conductive additive. Preferably, the carbon nanocage is a hierarchical carbon nanocage hCNC, and the resulting composite conductive agent is CB-hCNC.

[0011] Thirdly, the present invention provides a lithium-ion battery negative electrode, which is prepared by dissolving micron-sized silicon powder, carbon black, carbon nanocages, and a binder in water to form a homogeneous slurry, coating it onto a negative electrode current collector, and then vacuum drying it. Preferably, the binder is sodium carboxymethyl cellulose (CMC); more preferably, the mass ratio of the micron-sized silicon powder, carbon black (CB), hCNC, and CMC is 8:0.5:0.5:1. Preferably, the negative electrode current collector is copper foil. Preferably, the vacuum drying conditions are drying at 80°C in a vacuum oven for 12 hours.

[0012] Fourthly, this invention provides an effective solution for the volume expansion / contraction of silicon-based negative electrodes and the storage / release of electrolytes in lithium-ion batteries.

[0013] As a specific embodiment of the above-mentioned lithium-ion battery, the lithium-ion battery uses lithium iron phosphate (LiFePO4) as the positive electrode, and the electrolyte is 1 M lithium hexafluorophosphate (LiPF6) dissolved in a mixed solution, and Celgard 2500 is used as the separator; wherein, the mixed solution is a solution formed by mixing EC / DEC, fluoroethylene carbonate (FEC), and ethylene carbonate (VC), and the volume ratio of EC / DEC, FEC, and VC is 89:10:1; EC / DEC is prepared by mixing ethylene carbonate and diethyl carbonate in a volume ratio of 1:1.

[0014] As another specific implementation of the aforementioned lithium-ion battery, the sponge-like conductive additive's effect on improving the lithium storage performance of the micron-sized silicon anode is more significant under electrolyte-deficient conditions, where the electrolyte dosage is no higher than 10 μL mg. -1 .

[0015] Beneficial effects:

[0016] The present invention proposes to apply a sponge-like conductive additive to the silicon-based anode of lithium-ion batteries. The sponge-like conductive additive has the following technical advantages: (1) high conductivity; (2) good compressibility and resilience, which helps to accommodate the large volume change of Si-based materials during charging and discharging, reduce the volume expansion of the electrode, alleviate local stress and silicon powdering; (3) the unique pore structure can be used as a lithium-ion reservoir, and regulate the electrolyte distribution around the micron-sized silicon through a self-breathing mechanism, which is especially suitable for making micron-sized silicon anodes.

[0017] The sponge-like conductive additive composed of carbon black (CB) and hCNC proposed in this invention is particularly effective in addressing key issues in micron-sized silicon anodes, such as low conductivity, high stress, and drastic fluctuations in local lithium-ion concentration. Experimental results show that the composite additive composed of CB and hCNC effectively alleviates the aforementioned key problems by synergistically regulating structure and conductivity. The optimized Si-CB-hCNC anode exhibits excellent cycle stability in half-cell testing; for example, the experimental sample showed good cycle stability at 0.2 A g. -1 The capacity is 1195 mAh g after 200 cycles at current density. -1 ; in 4 A g -1 The capacity is 690 mAh g after 700 cycles at current density. -1 It also performs excellently in full cells used in combination with lithium iron phosphate (LiFePO4) cathodes; for example, the experimental sample achieved a capacity of 125.5 mAh g after 550 cycles at 1 C rate. -1 It also possesses improved rate performance. Its significantly enhanced lithium storage performance is attributed to the synergistic effect of the composite CB-hCNC conductive agent: First, the excellent compressibility and recoverability of hCNC effectively mitigate the large volume changes of Si-based materials during cycling, reducing electrode volume expansion, mechanical stress, and silicon fragmentation; second, the internal cavity structure of hCNC can act as a lithium-ion reservoir, achieving localized control of electrolyte concentration on the micron-scale silicon surface through a self-breathing mechanism; third, the high conductivity of CB-hCNC facilitates rapid and efficient charge transport within the electrode. This performance enhancement strategy can be further applied to other alloying / conversion electrode materials. Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the lithiation / delithiation process of silicon when using traditional solid carbon black additives in the background technology. The blue intensity corresponds to the Li⁺ concentration in the electrolyte, and the red arrows indicate the migration direction of Li⁺.

[0019] Figure 2 This is a schematic diagram of the lithiation / delithiation process of silicon when using sponge-like hCNC additives in this invention. The red arrows indicate the migration direction of Li⁺.

[0020] Figure 3 The image shown is a scanning electron microscope (SEM) image of the raw material using hCNC scanning electron microscopy, and the inset in the upper right corner is the corresponding transmission electron microscope (TEM) image.

[0021] Figure 4 The image shown is a scanning electron microscope (SEM) image of the raw material CB, and the inset in the upper right corner is the corresponding transmission electron microscope (TEM) image.

[0022] Figure 5 The image shown is a scanning electron microscope (SEM) image of the raw material CNTs, and the inset in the upper right corner is the corresponding transmission electron microscope (TEM) image.

[0023] Figure 6 The physical properties of raw materials hCNC, CB, and CNT include conductivity.

[0024] Figure 7 The physical properties and pore size distribution of raw materials hCNC, CB and CNT;

[0025] Figure 8 Compression ratios under different pressures based on the physical properties of raw materials hCNC, CB, and CNT;

[0026] Figure 9 XRD patterns of raw materials hCNC, CB and CNT;

[0027] Figure 10 Raman spectra of raw materials hCNC, CB and CNT;

[0028] Figure 11 Nitrogen adsorption-desorption isotherms for raw materials hCNC, CB and CNT;

[0029] Figure 12 XRD characterization of micron-sized silicon;

[0030] Figure 13 The Raman spectrum of micron-sized silicon;

[0031] Figure 14 For micron-sized silicon at 20 mL·min -1 TGA curves were obtained at the flow rate and under a 20 vol.% O2 / N2 atmosphere.

[0032] Figure 15 The N2 adsorption-desorption isotherm for micron-sized silicon (Si);

[0033] Figure 16 The pore size distribution of micron-sized silicon (micron-Si);

[0034] Figure 17Low-magnification scanning electron microscope (SEM) image of micron-sized silicon (micron-Si);

[0035] Figure 18 High-magnification scanning electron microscope (SEM) image of micron-sized silicon (micron-Si);

[0036] Figure 19 The rate performance of the half-cell assembled from Si-CB, Si-CB-hCNC, Si-hCNC and Si-CB-CNT in Experimental Example 1;

[0037] Figure 20 The cycling performance of the half-cells assembled from Si-CB, Si-CB-hCNC, Si-hCNC and Si-CB-CNT in Experimental Example 1 at a current density of 1 A·g⁻¹.

[0038] Figure 21 The cycling performance of the half-cells assembled from Si-CB, Si-CB-hCNC, Si-hCNC and Si-CB-CNT in Experimental Example 1 at a current density of 4 A·g⁻¹.

[0039] Figure 22 Nyquist plots for the in-situ EIS evolution of Si-CB, Si-CB-hCNC, Si-hCNC and Si-CB-CNT during the cyclic process in Experimental Example 2, specifying the number of cycles.

[0040] Figure 23 The in-situ EIS evolution of Si-CB, Si-CB-hCNC, Si-hCNC and Si-CB-CNT during the cycling process in Experiment Example 2 is shown in the corresponding curves of Rs, Rf and Rct. The inset is the equivalent circuit used to fit the EIS spectrum.

[0041] Figure 24 The electrochemical and cycling performance of Si-CB, Si-CB-hCNC, Si-hCNC and Si-CB-CNT were tested in Experiment Example 4 using lean electrolyte. Figure 25 The electrochemical and rate performance of Si-CB, Si-CB-hCNC, Si-hCNC and Si-CB-CNT were tested in Experiment Example 4 using a lean electrolyte. Figure 26 The amount of electrolyte absorbed by different silicon anodes, namely Si-CB, Si-CB-hCNC, Si-hCNC and Si-CB-CNT, when using lean electrolyte in Experiment Example 4; Figure 27 The electrochemical performance of CB, hCNC and CNT in Experimental Example 1; Figure 28The figures show the electrode thickness changes of Si-CB, Si-CB-hCNC, Si-hCNC, and Si-CB-CNT before and after 200 cycles in Experiment Example 3. Figures a to d are the side-view SEM images of Si-CB, Si-CB-hCNC, Si-hCNC, and Si-CB-CNT in their initial states, respectively; Figures e to h are the corresponding side-view SEM images after 200 cycles, respectively.

[0042] Figure 29 These are conventional transmission electron microscopy (TEM) and high-resolution TEM images of tCNC in Experiment Example 3.

[0043] Figure 30 The rate performance of the Si-CB-tCNC and Si-tCNC group half-cells in Experiment Example 3;

[0044] Figure 31 For the half-cells of Si-CB-tCNC and Si-tCNC groups in Experiment Example 3, at 1 A g -1 Cyclic performance at current density;

[0045] Figure 32 For the half-cells of Si-CB-tCNC and Si-tCNC groups in Experiment Example 3, at 4 A g -1 Cyclic performance at current density;

[0046] Figure 33 These are HRTEM images of the Si-CB-tCNC and Si-CB-hCNC electrodes in Experiment Example 3 after 200 cycles.

[0047] Figure 34 The reaction rate performance of the Si-CB-hCNC|| LFP full cell in Experimental Example 5;

[0048] Figure 35 The cycling performance of the Si-CB-hCNC|| LFP full cell at 1C rate is shown in Experimental Example 5. Detailed Implementation

[0049] The present invention will now be described in detail with reference to experimental examples to facilitate understanding of the invention by those skilled in the art. It is important to emphasize that the experimental examples are merely for further illustration and should not be construed as limiting the scope of protection of the invention. Non-essential improvements and adjustments made to the invention based on the above description should still fall within the scope of protection of the invention. Furthermore, all raw materials mentioned below, unless otherwise specified, are commercially available products; and all process steps or extraction methods not mentioned in detail are process steps or extraction methods known to those skilled in the art.

[0050] Main test methods and test equipment:

[0051] The structure and composition of the following samples were characterized using the following methods: scanning electron microscopy (Hitachi S4800), HRTEM (JEM-2100), XRD (Bruker D2 Phaser, Cu Kα1 radiation mode, equipped with a LYNXEYE XE-T detector with a resolution of 380 eV), X-ray photoelectron spectroscopy (XPS, ULVAC-PHI INC, PHI 5000VersaProbe, Al Kα), and thermogravimetric analysis (Netsch STA449F3, oxygen / nitrogen flow ratio of 1:5, flow rate of 20 mL / min). - ¹, Heating rate 10.0℃ min - ¹) and nitrogen adsorption / desorption isotherm measurements (Thermo Fisher Scientific Surfer gas adsorption porosity meter, measured at 77 K after degassing at 300 °C for 6 hours). Specific surface area and pore size distribution were estimated based on adsorption branch data using the Brunauer-Emmett-Teller (BET), Horvath-Kawazoe (HK, <2 nm micropores), and Barrett-Joyner-Halenda (BJH, >2 nm pores) methods, respectively.

[0052] Main raw material sources, preparation methods, and characterization:

[0053] The hCNC samples used in the following examples were all synthesized using a benzene precursor via an in-situ magnesium oxide template method. The specific preparation steps are consistent with those in our previously published literature, “Lyu, Z., Xu, D., Yang, L., et al., "Hierarchical carbon nanocages confining high-loading sulfur for high-rate lithium–sulfur batteries," Nano Energy 12 (2015): 657.” In short, 8 g of basic magnesium carbonate (4MgCO3·(OH)2·5H2O) was placed in a quartz tube in a vertical furnace and heated at 10 °C for 1 min under an argon flow. -1 The sample was heated to 800°C at a controlled heating rate. Then, 1 mL of benzene was slowly injected, and the temperature was maintained for 1 hour. After cooling to room temperature, the sample was washed with 3 M hydrochloric acid and deionized water. hCNC was obtained after freeze-drying for 24 hours.

[0054] The preparation process of tCNC is the same as that of hCNC, except that the amount of benzene injected is 0.3 mL.

[0055] CB and CNT were purchased from Shanghai Xiding Biotechnology Co., Ltd. and Canrd Co., Ltd., respectively.

[0056] The morphology and physical properties of samples hCNC, CB, and CNT have been characterized: such as Figure 3 As shown, hCNC consists of porous spherical particles assembled from nanosheets, which are composed of hollow nanocages with a size of 20-40 nm; Figure 4 CB exhibits a solid spherical shape without hierarchical structure; such as Figure 5 As shown, CNTs have a typical tubular structure with a diameter of 10-20 nm and are arranged in a cocoon-like pattern. Figure 9 and Figure 10 The X-ray diffraction (XRD) and Raman spectroscopy analyses shown indicate that all three materials exhibit a high degree of graphitization. Figure 6 The four-wire method measurements shown indicate that their conductivity is comparable, with an average value of 1350 S / m. -1 Therefore, it is suitable for use as a conductive agent. However, as... Figure 7 and Figure 8 As shown, their different morphological features lead to differences in pore structure and mechanical properties. Figure 11 The nitrogen adsorption / desorption experiments shown indicate that hCNC has the highest Bruner-Emmett-Taylor specific surface area (SBET) and the largest pore volume (2.36 cm³ g) as shown in Table S1. -1 . Figure 8 The compression ratio versus pressure curves shown indicate that both hCNC and CNT exhibit superior compressibility compared to CB, reflecting their higher compression recovery capabilities. The large pore volume and high compressibility of hCNC offer significant advantages in mitigating the stress / strain caused by volume expansion of silicon materials during lithiation.

[0057] Table S1: Specific surface area and pore volume of CB, hCNC, CNT and micron-sized silicon

[0058]

[0059] The micron-sized silicon used was prepared by etching Mg2Si particles in hydrochloric acid solution, followed by carbon coating. Synthesis of micron-sized silicon: Micron-sized silicon was prepared by chemical etching and carbon coating. Typically, 1.5 g of MgSi2 was dispersed in 50 mL of deionized water, followed by dropwise addition of 300 mL of 1 M hydrochloric acid aqueous solution and stirring for 12 hours. The pSi sample was obtained by filtration, repeated washing with deionized water, and drying at 80°C for 6 hours. The obtained pSi was then mixed with coal tar at a mass ratio of 5:1 in THF and stirred for 24 hours. After removing the THF solvent by rotary evaporation at 40°C, the sample was heat-treated at 800°C for 3 hours under argon protection to finally obtain the micron-sized silicon sample. Figure 12 , Figure 13 and Figure 14 The various characterization methods shown indicate that this micron-sized silicon is composed of Si (88.3%), C, and O elements, and possesses a high-purity elemental silicon crystal structure. For example... Figure 15 , Figure 16 , Figure 17 and Figure 18 The nitrogen adsorption / desorption experiments and scanning electron microscopy observations shown both confirmed that it has a porous structure with a particle size of 5–10 μm. Its low specific surface area (43.9 m² g / g) -1 ) and pore volume (0.09 cm³ g) -1 This gives micron-sized silicon a high packing density (0.531 g cm⁻¹). - (³), which also helps to suppress side reactions.

[0060] Experimental Example 1

[0061] To elucidate the effects of different additives on the lithium storage performance of micron-sized silicon electrodes, half-cells were assembled using pure CB, pure hCNC, a CB-hCNC mixed conductive agent, and a CB-CNT mixed conductive agent mixed with micron-sized silicon. The assembled half-cell samples were divided into four groups: control group Si-CB, experimental group Si-hCNC, experimental group Si-CB-hCNC, and control group Si-CB-CNT. The Si-CB-hCNC electrode was prepared by dissolving micron-sized silicon powder, carbon black (CB), hCNC, and sodium carboxymethyl cellulose (CMC) in deionized water at a mass ratio of 8:0.5:0.5:1. The homogeneous slurry was coated onto copper foil and then dried in a vacuum oven at 80°C for 12 hours. The preparation processes for the Si-CB-CNT and Si-CB-tCNC electrodes were the same, except that CNT and tCNC replaced hCNC, respectively. The Si-CB, Si-hCNC, and Si-tCNC electrodes were fabricated using the above-described process, but the mass ratio of micron-sized silicon powder, CB (or hCNC), and CMC was adjusted to 8:1:1. The active material mass loading for all electrodes was approximately 1.02 mg cm⁻¹.-2 Then, the four sets of electrodes were used to assemble half-cells, with 50 μL mg electrolyte. -1 1 M lithium hexafluorophosphate (LiPF6) was dissolved in a solution containing 89 vol.% ethylene carbonate and diethyl carbonate (EC / DEC) (1:1, v / v), 10 vol.% fluoroethylene carbonate (FEC) and 1 vol.% ethylene carbonate (VC); a coin-shaped (CR2032) half-cell was assembled using lithium foil as the counter electrode.

[0062] Micron-sized silicon anodes undergo pre-lithiation treatment to improve initial coulombic efficiency (ICE) and compensate for irreversible lithium loss during the first cycle. Specifically, the initial anode sheet is assembled into a battery using lithium foil as the counter electrode. After one charge-discharge cycle, the battery is disassembled to obtain the pre-lithiated micron-sized silicon anode.

[0063] like Figure 27 As shown, CB, hCNC, and CNT all have relatively low specific capacities, indicating that the high specific capacity of these silicon anodes mainly originates from micron-sized silicon materials. Figure 19 As shown, in the rate performance test, Si-CB-hCNC exhibited the highest discharge capacity at current densities of 0.2, 0.4, 1, 2, 4 and 10 A·g⁻¹: 1412, 1359, 1237, 1088, 846 and 453 mAh·g⁻¹, respectively. It can be seen that the rate performance of Si-CB-hCNC is better than that of Si-CB, Si-hCNC and Si-CB-CNT.

[0064] In cyclic performance evaluation, such as Figure 20 As shown, the Si-CB-hCNC composite material exhibits the highest discharge capacity of 1195 mAh·g⁻¹ after 200 cycles at a current density of 0.2 A·g⁻¹, and retains a capacity of 894 mAh·g⁻¹ after 600 cycles at a current density of 1 A·g⁻¹. The Si-hCNC composite material retains a capacity of 825 mAh·g⁻¹ after 500 cycles at a current density of 1 A·g⁻¹, and its capacity retention rate is approximately 78.1% after 600 cycles at a current density of 1 A·g⁻¹. It is worth noting that, as... Figure 21 As shown, after 700 cycles at a current density of 4 A·g⁻¹, the Si-CB-hCNC composite material even achieved a high capacity of up to 690 mAh·g⁻¹ and a capacity retention of approximately 80.3%.

[0065] The above results show that, compared with the use of CB or CB-CNT, both hCNC or CB-hCNC composite conductive agents significantly improve the cycle performance of micron-sized silicon-based anodes. However, considering all the above performance, the CB-hCNC composite conductive agent significantly improves the lithium storage performance of micron-sized silicon-based anodes.

[0066] Experimental Example 2: The Influence of Different Materials on Electrode Charge Transfer Behavior

[0067] The effects of different materials on electrode charge transfer behavior were investigated using in-situ electrochemical impedance spectroscopy (EIS). Four groups of half-cell samples prepared in Experimental Example 1 were used for testing, and the results are shown below. Figure 22 and Figure 23 The results show that using carbon black (CB) as a conductive agent significantly promotes electron transfer, as evidenced by the low contact resistance (Rs) of the silicon-based anode; while the introduction of high-carbon nanotubes (hCNC) only slightly increases Rs, a result consistent with... Figure 6 The overall conductivity data for these materials are consistent. Compared to Si-CB and Si-CB-CNT, the addition of hCNC (i.e., Si-CB-hCNC and Si-hCNC) to micron-scale silicon anodes effectively reduces the interfacial resistance Rf of the SEI film. This is attributed to the fact that hCNC can alleviate stress generated during cycling, thereby suppressing silicon particle fragmentation and improving the structural stability of the SEI film. Si-CB-hCNC exhibits the lowest charge transfer resistance Rct due to its synergistic effect: the multi-point contact between the hybrid CB-hCNC conductive agent and silicon particles promotes electron transfer, while its porous structure facilitates ion transport. Furthermore, as... Figure 23 As shown, the Si-CB-hCNC anode exhibits the most stable equivalent series resistance, R, during cycling. ESR = Rs + Rf + Rct, which is the key to its excellent cyclic stability.

[0068] Experimental Example 3: The Effect of Compressible / Recoverable hCNC on the Cyclic Performance of Micron-Sized Silicon Anodes

[0069] Further research was conducted on the role of hCNC in improving the lithium storage performance of micron-sized silicon anodes. Four sets of half-cell samples prepared in Experimental Example 1 were tested. Visually, the porous structure of hCNC can alleviate the stress caused by the volume expansion of silicon particles. The thickness change of the silicon electrode before and after lithiation was measured. Figure 28As shown, the specific values ​​of the volume change rate during cycling and the change rate of electrode thickness can be obtained: 59.9% for the Si-CB group, 12.5% ​​for the Si-CB-hCNC group, 11.0% for the Si-hCNC group, and 26.9% for the Si-CB-CNT group. The study found that under the same mass load, due to the lower density of hCNC, the silicon anodes prepared with hCNC are all thicker than those prepared with Si-CB and Si-CB-CNT. After lithiation, the increase in electrode thickness for Si-CB-hCNC and Si-hCNC is much smaller than that for Si-CB and Si-CB-CNT. This result clearly indicates that hCNC plays a key role in significantly suppressing the overall volume expansion of the silicon electrode, thereby significantly improving cycling stability. It can be inferred that the compression / recovery capability of hCNC is crucial to the cycling stability of micron-sized silicon anodes. For comparison, a thinner carbon nanocage material, tCNC, was prepared, such as... Figure 29 The images shown are TEM and HRTEM images of the tCNC sample. Figure 30 , Figure 31 and Figure 32 The results show that the cycle performance of Si-CB-tCNC is significantly inferior to that of Si-CB-hCNC. Figure 33 Morphological analysis after cyclic testing showed that the tCNC collapsed due to insufficient recovery capability and could not withstand the significant stress during cycling, thus losing its reinforcing effect. This result further confirms the significant improvement effect of compressible / recoverable hCNC on the cycling performance of micron-sized silicon anodes.

[0070] Experiment Example 4: Lithium Storage Performance Test under Different Electrolyte Conditions

[0071] Using the same fabrication method as the four sets of half-cell samples in Experiment 1, the only difference being that the electrolyte concentration in this experiment was 10 µL mg⁻¹, four sets of half-cell samples under electrolyte-deficient conditions were assembled and tested. It can be seen that the improvement effect of hCNC on the lithium storage performance of micron-sized silicon anodes is more significant under electrolyte-deficient conditions: Figure 24 As shown, when the electrolyte concentration is only 10 µL mg⁻¹, Si-CB-hCNC still maintains a high specific capacity of 989.2 mAh g⁻¹ after 400 cycles at a current density of 1 A g⁻¹, with a capacity retention of 80.1%, exhibiting the best electrochemical performance among all comparative materials. Figure 25 As shown, even at current densities as high as 4 A g⁻¹, Si-CB-hCNC can still maintain a high capacity of 628.1 mAh g⁻¹.

[0072] Compared to the performance shown under electrolyte-rich conditions in Example 1, Si-CB-hCNC maintained excellent high capacity and rate performance under electrolyte-poor conditions, while Si-CB, Si-CB-CNT, and Si-hCNC anodes exhibited significant performance degradation. This result reveals another important role of hCNC in enhancing the cycle stability of micron-sized silicon anodes: regulating the local lithium-ion concentration in the electrolyte. It is well known that under electrolyte-poor conditions, depleted lithium ions around the silicon surface cannot be quickly replenished from the surrounding environment, leading to stagnation of the lithiation reaction and capacity decay. In the Si-CB-hCNC anode, this sponge-like hCNC not only promotes electron transfer but also acts as an electrolyte reservoir to provide lithium ions for the lithiation process. Electrolyte absorption experiments show that the anode containing hCNC, due to its high pore volume, Figure 26 The CB-hCNC composite conductive agent can absorb more electrolyte. Compared with hCNC alone, the CB-hCNC composite conductive agent has significant advantages in electrochemical performance, highlighting the further synergistic and complementary effects of the composite conductive agent: carbon black is mainly responsible for promoting electron transport, while the compressible hCNC has a dual function, namely, it can accommodate the volume expansion of the active material and act as an electrolyte reservoir. Specifically, during discharge, the volume expansion of silicon causes part of the electrolyte to be discharged from the inside of the nanocage, thereby replenishing the lithium ions consumed during lithiation. During charging, the elastic recovery properties of the hCNC material can maintain a tight electrical contact between the silicon particles and the conductive network, and effectively accommodate the large amount of lithium ions (Li) released during delithiation. + This prevents lithium salt precipitation. The self-breathing behavior of this CB-hCNC additive not only alleviates stress / strain caused by volume changes and improves electrical connection performance, but also regulates the electrolyte state, thereby enabling the micron-sized silicon anode to exhibit excellent cycle stability in lithium storage applications.

[0073] Experiment Example 5: Full Battery Assembly Experiment

[0074] The Si-CB-hCNC electrode was prepared using the same method as in Experimental Example 1, employing lithium foil as the counter electrode to assemble a coin-shaped (CR2032) half-cell; and LiFePO4 as the positive electrode to assemble a full cell. The electrolyte consisted of 1 M lithium hexafluorophosphate (LiPF6) dissolved in a solution containing 89 vol.% ethylene carbonate and diethyl carbonate (EC / DEC) (1:1, v / v), 10 vol.% fluoroethylene carbonate (FEC), and 1 vol.% ethylene carbonate (VC), with a Celgard 2500 membrane used. Under standard conditions, the electrolyte volume was 50 μL mg. -1 The dosage under lean electrolyte conditions is 10 μL mg. -1The batteries were allowed to stand for 12 hours before measurement. Half-cells were tested using a NEWARE CT4008T multichannel battery testing system with constant current charge-discharge in the potential range of 0.01–1.00 V (relative to Li / Li⁺); full cells were tested in the voltage range of 2.5–3.8 V. The tests were conducted on a Bio-logic electrochemical workstation (VMP-300) at a rate of 0.1–1.0 mV·s. -1 Cyclic voltammetry curves were tested at a scan rate of 100 kHz to 0.1 Hz; EIS spectra were recorded with an amplitude of 5 mV in the frequency range of 100 kHz to 0.1 Hz.

[0075] The practical application performance of Si-CB-hCNC was further verified in a full cell composed of LiFePO4 (LFP), such as... Figure 34 As shown, when the cutoff voltage is 2.5 V, the Si-CB-hCNC|| LFP full cell exhibits 169.7, 155.7, 140.2, 122.3, 98.1, and 61.4 mAh·g at rates of 0.1, 0.2, 0.5, 1, 2, and 5C, respectively. -1 Specific capacity (1 C = 170 mAh·g) -1 ). Figure 35 As shown, after 550 cycles, the full cell still maintains 125.5 mAh·g at 1 C rate. -1 The high capacity and capacity retention rate of 97.4% fully demonstrate the great potential of CB-hCNC conductive agent in silicon-based anodes.

Claims

1. The application of a sponge-like conductive additive in silicon-based anodes, characterized in that, The sponge-like conductive additive is a hierarchical carbon nanocage material, which is a three-dimensional ordered hierarchical conductive network structure with interconnected macropores, mesopores and micropores, assembled from individual carbon nanocages (CNC) as basic building units; the silicon-based anode refers to a type of anode material that uses silicon or silicon-containing compounds as the main active material and achieves energy storage through alloying and dealloying reactions with lithium.

2. The application as described in claim 1, characterized in that, The carbon nanocage is a hierarchical carbon nanocage hCNC.

3. The application as described in claim 1, characterized in that, The silicon-based negative electrode is micron-sized silicon.

4. A composite conductive agent, characterized in that, The composite conductive agent comprises a sponge-like conductive additive and carbon black CB, and is used in silicon-based anodes. The sponge-like conductive additive is a hierarchical carbon nanocage material, which is a three-dimensional ordered hierarchical conductive network structure with interconnected macropores, mesopores and micropores, assembled from individual carbon nanocages (CNC) as basic building blocks.

5. The composite conductive agent as described in claim 4, characterized in that, The aforementioned sponge-like conductive additive is a graded carbon nanocage hCNC, and the resulting composite conductive agent is CB-hCNC.

6. A lithium-ion battery negative electrode, characterized in that, The lithium-ion battery anode is prepared by dissolving micron-sized silicon powder, carbon black CB, carbon nanocages hCNC and binder in water to form a homogeneous slurry, which is then coated onto the anode current collector and subsequently vacuum dried.

7. The lithium-ion battery negative electrode as described in claim 6, characterized in that, The binder is sodium carboxymethyl cellulose (CMC), and the mass ratio of the raw materials, namely micron-sized silicon powder, carbon black (CB), hCNC, and CMC, is 8:0.5:0.5:

1. The negative electrode current collector is copper foil, and the vacuum drying conditions are drying at 80°C for 12 hours in a vacuum oven.

8. A lithium-ion battery, characterized in that, The lithium-ion battery includes the lithium-ion battery negative electrode as described in claim 6.

9. The lithium-ion battery as described in claim 8, characterized in that, The lithium-ion battery uses LiFePO4 as the positive electrode, and lithium iron phosphate (LiFePO4) is used as the positive electrode. The electrolyte is 1 M lithium hexafluorophosphate (LiPF6) dissolved in a mixed solution, and Celgard 2500 is used as the separator. The mixed solution is a solution formed by mixing EC / DEC, fluoroethylene carbonate (FEC), and ethylene carbonate (VC), and the volume ratio of EC / DEC, FEC, and VC is 89:10:

1. EC / DEC is prepared by mixing ethylene carbonate and diethyl carbonate in a volume ratio of 1:

1.

10. The lithium-ion battery as described in claim 8, characterized in that, The electrolyte used in the lithium-ion battery is under lean electrolyte conditions, with a dosage not exceeding 10 μL mg. -1 .